Identifying and Exploring Jean Watson's Theory of Human Caring in Nursing Approaches for Patients with Psychoactive Substance Dependence in Medical and Surgical Acute Wards - Felice Curcio; Marzia Lommi; Rosa Nury Zambrano Bermeo; Ana Alejandra Esteban-Burgos; Gianluca Pucciarelli; Cesar Iván Avilés González (MDPI AG, 2024)
Patients with substance use disorders may view healthcare professionals as capable of supporting them through their suffering and experience. Although numerous studies have focused on the roles, approaches, and attitudes of healthcare professionals, there is a lack of information on the nursing perspective. This study aims to explore the experiences and nursing approaches towards patients with psychoactive substance dependence admitted to an Italian acute hospital ward. A qualitative phenomenological study was conducted. Data were collected using semi-structured face-to-face interviews. The interviews were transcribed, read thoroughly, and analysed. Fifteen nurses were interviewed. Six main themes were extracted: (1) origin context, (2) participants' personal thoughts, (3) type of approach provided, (4) school education received on the topic, (5) effectiveness of rehabilitative therapy, and (6) methods that can improve nursing care. The findings suggest that most respondents experience stigma and discrimination when providing care to these patients. In response to the results obtained, models have been suggested, such as Jean Watson's Human Caring Theory, which shows how practising a holistic approach based on empathy and active listening can improve the relationship between nurses and patients. Furthermore, to eliminate stereotypes, it would be appropriate to act on the university education of nurses. This study was not registered.